Fishy childhoods in space and time: intergenerational continuities and changes. Issue 1 (2nd January 2023) - Spyrou, Spyros; Theodorou, Eleni; Stylianidou, Nayia
ABSTRACT: This article is based on research conducted in a small fishing community in Cyprus. It seeks to explore through an intergenerational and biographical approach how three generations of Greek Cypriot males belonging to fishing families create a meaningful sense of identity through their attachment to place and the fishing profession. The article analyses these three generations' childhood experiences, their social relationships and the processes of learning and knowledge transmission at work, to trace inter- and intra-generational changes and continuities and to offer a more nuanced understanding of the younger generation's sense of identity and belonging in light of ongoing structural changes. Findings pinpoint the centrality of place – land and sea – in all generations' sense of belonging and a strong sense of attachment to fishing which is, however, impacting the younger generation's professional orientations at an emotional level, given that fishing is no longer viable as a profession.